2017
DOI: 10.1002/cjoc.201700477
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Amide Ligands Enable Cu‐Catalyzed Coupling of Sodium Methanesulfinate with (Hetero)aryl Chlorides

Abstract: ((2S,4R)‐4‐Hydroxy‐N‐(2‐methylnaphthalen‐1‐yl)pyrrolidine‐2‐carboxamide (HMNPC), an amide derived from 4‐hydroxy‐L‐proline and 2‐methyl naphthalen‐1‐amine, is a powerful ligand for Cu‐catalyzed coupling of (hetero)aryl halides with sulfinic acid salts, allowing for first time the metal‐catalyzed coupling of (hetero)aryl chlorides and NaSO2Me. A considerable number of (hetero)aryl chlorides worked well, providing the pharmaceutically important (hetero)aryl methylsulfones in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Initially, we examined (2S,4R)-4-hydroxy-N-(2-methylnaphthalen-1-yl)pyrrolidine-2-carboxamide (L1, HMNPC), 14 the best ligand for Cu-catalyzed coupling reaction of (hetero)aryl chlorides and sodium methanesulfinate. It was found that under the action of 2 mol % CuI and L1, the reaction completed after 24 h at 100 °C to afford 1-methoxy-4-(phenylsulfonyl)benzene (2a) in 99% yield (entry 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Initially, we examined (2S,4R)-4-hydroxy-N-(2-methylnaphthalen-1-yl)pyrrolidine-2-carboxamide (L1, HMNPC), 14 the best ligand for Cu-catalyzed coupling reaction of (hetero)aryl chlorides and sodium methanesulfinate. It was found that under the action of 2 mol % CuI and L1, the reaction completed after 24 h at 100 °C to afford 1-methoxy-4-(phenylsulfonyl)benzene (2a) in 99% yield (entry 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because CuI/ l -proline could not efficiently catalyze the coupling of (hetero)­aryl bromides and relatively bulky sodium benzenesulfinate, we chose the coupling of 4-bromoanisole with sodium benzenesulfinate as a model reaction to screen suitable ligands, and the results are summarized in Table . Initially, we examined (2 S ,4 R )-4-hydroxy- N -(2-methylnaphthalen-1-yl)­pyrrolidine-2-carboxamide ( L1 , HMNPC), the best ligand for Cu-catalyzed coupling reaction of (hetero)­aryl chlorides and sodium methanesulfinate. It was found that under the action of 2 mol % CuI and L1 , the reaction completed after 24 h at 100 °C to afford 1-methoxy-4-(phenyl­sulfonyl)­benzene ( 2a ) in 99% yield (entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations